2022
DOI: 10.3390/jof8060586
|View full text |Cite
|
Sign up to set email alerts
|

Crop Rotation and Minimal Tillage Selectively Affect Maize Growth Promotion under Late Wilt Disease Stress

Abstract: In recent years, worldwide scientific efforts towards controlling maize late wilt disease (LWD) have focused on eco-friendly approaches that minimize the environmental impact and health risks. This disease is considered to be the most severe threat to maize fields in Israel and Egypt, and a major growth restraint in India, Spain, and Portugal. Today’s most commonly used method for LWD control involving resistant maize genotypes is under constant risk from aggressive pathogen lines. Thus, this study’s objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…The inoculation procedure consisted, besides naturally infected soil, three steps of complementary inoculation addition: (1) Pre-seeded soil was infected with sterilized pathogen-inoculated wheat grains, prepared as previously described [ 19 , 20 ]. The soil was infected by blending 20 g of the infected sterilized wheat grains with the soil’s top 10 cm layer; (2) two mycelia colony disks (see Section 2.1 ) from F. oxysporum f. sp.…”
Section: Methodsmentioning
confidence: 99%
“…The inoculation procedure consisted, besides naturally infected soil, three steps of complementary inoculation addition: (1) Pre-seeded soil was infected with sterilized pathogen-inoculated wheat grains, prepared as previously described [ 19 , 20 ]. The soil was infected by blending 20 g of the infected sterilized wheat grains with the soil’s top 10 cm layer; (2) two mycelia colony disks (see Section 2.1 ) from F. oxysporum f. sp.…”
Section: Methodsmentioning
confidence: 99%
“…The inoculation method consisted of naturally infected soil and complementary infection conducted in three steps to guarantee a high and uniform infection load. First, pre-sowing soil was inoculated with sterilized infected wheat grains that had been prepared as previously described [20,21]. Briefly, the wheat seeds were soaked in tap water overnight, filtered, and dried.…”
Section: Complementary Inoculationmentioning
confidence: 99%
“…For example, due to the well-developed rooting action of perennial forage grasses, the organic matter content of some farmland in maize-forage rotations was significantly higher than under monoculture maize cropping patterns [15,16]. Crop rotation can effectively improve soil nutrient content and enzyme activity [17][18][19] and change the diversity and structure of soil microbial communities [20,21] through the impacts of root exudates and crop residues, which are effective at reducing crop succession barriers [22]. One relevant study suggested that bacteria and fungi in soils generally account for more than 90% of all the soil microbial population [23], and some organic matter conversion processes in soils are controlled by soil microbial communities [24][25][26].…”
Section: Introductionmentioning
confidence: 99%